The critical few : energize your company's culture by choosing what really matters - Katzenbach, Jon R., 1932-; Thomas, James; Anderson, Gretchen (Berrett-Koehler Publishers, Inc., 2018)
In a global survey by the Katzenbach Center, 80 percent of respondents believed that their organization must evolve to succeed. But a full quarter of them reported that a change effort at their organization had resulted in no visible results. Why? The fate of any change effort depends on whether and how leaders engage their culture: the self-sustaining patterns of behaving, feeling, thinking, and believing that determine how things are done in an organization. Culture is implicit rather than explicit, emotional rather than rational--that's what makes it so hard to work with, but that's also what makes it so powerful. For the first time, this book lays out the Katzenbach Center's proven methodology for identifying your culture's four most critical elements: traits, characteristics that are at the heart of people's emotional connection to what they do; keystone behaviors, actions that would lead your company to succeed if they were replicated at a greater scale; authentic informal leaders, people who have a high degree of "emotional intuition" or social connectedness; and metrics, integrated, thoughtful measures to track progress, encourage the self-reinforcing cycle of lasting change and link to business performance. By leveraging these critical few elements, you can tap into a source of catalytic change within your organization. People will make an emotional, not just a rational, commitment to new initiatives. You will elicit enthusiasm and creativity and build the kind of powerful company that people recognize for its innate value and effectiveness